東醫寶鑑 부종편의 원문과 인용문헌에 대한 비교고찰 - 양준석(Jun Suk Yang); 고형곤(Hyoung Gon Ko); 진재호(Jae Ho Jin); 한웅(Woong Han); 정상훈(Sang Hun Jeong); 김호(Ho Kim); 이동주(Dong Ju Lee); 이광규(Kwang Gyu Lee) (동의생리병리학회지, 2004)
We studied on the purpose of comparing the original texts with quotations in edema chapter of Dong-Yi-Bo-Gam. The research mainly depended on compare and consider these original text and quote. In Pyong Yeol Byong chapter of SoMoon, Su Yeol Hyul chapter of SoMoon, Pyong Yin Ki Sang chapter of SoMoon, Ja Jeol Jin Sae chapter of YoungChu, Emperor‘s Classic of Internal Medicine(黃帝內經;ECIM), We were able to find that some sentences about edema were quoted. Drug arrangement order that construct herb medicine is disposed depends on drug's weight, and all unit was concorded by Jeon and Pun. Quoted words in Emperor‘s Classic of Internal Medicine(黃帝內經;ECIM) does not perfectly match with original text. However, edema chapter of Dong-Yi-Bo-Gam is identical with original text, because only few words were deleted or inserted. KCI Citation Count: 3